High-throughput fluorescence polarization immunoassay by using a portable fluorescence polarization imaging analyzer. Issue 15 (28th June 2019) - Wakao, Osamu; Satou, Ken; Nakamura, Ayano; Galkina, Polina A.; Nishiyama, Keine; Sumiyoshi, Ken; Kurosawa, Fumio; Maeki, Masatoshi; Ishida, Akihiko; Tani, Hirofumi; Proskurnin, Mikhail A.; Shigemura, Koji; et al.
Abstract : A portable fluorescence polarization imaging analyzer was developed for high-throughput fluorescence polarization immunoassay. Abstract : High-throughput fluorescence polarization immunoassays (FPIAs) for mycotoxin were conducted using a portable FP analyzer with a microdevice. Simultaneous FPIA measurements for 8 different deoxynivalenol (DON) concentrations in 12 chambers (total of 96 samples) and high-throughput FPIA measurements for single DON concentrations in more than 500 chambers were conducted. The results indicated that simultaneous FPIAs for 96 independent samples and for 500 samples were possible by FP imaging. The FP analyzer has a size of 65 cm (W 35 cm × D 15 cm × H 15 cm) and costs less than 5000. The sample volume was 1 nL. Furthermore, it is expected that sample reaction and FP detection can be automatically conducted with the analyzer by changing the microdevice and the software. Its features such as low cost and portability will contribute to on-site measurement and point-of-care testing. Additionally, the high-throughput feature will contribute to the study of molecular interactions based on FP measurements.